How can signaling in authentic classroom videos support reasoning on how to induce learning strategies? - Tannert, Swantje; Eitel, Alexander; Marder, Johanna; Seidel, Tina; Renkl, Alexander; Glogger-Frey, Inga (Frontiers in Education, 2023)
Classroom videos are a viable means to implement evidence-informed reasoning in teacher education in order to establish an evidence-informed teaching practice. Although learning with videos relieves pre-service teachers from acting in parallel and might reduce complexity, the material still poses higher cognitive load than written text vignettes or other traditionally used static material. In particular, the information they deliver is transient and can, therefore, easily be missed. Signaling can guide learners’ attention to central aspects of a video, thereby reducing cognitive load and enhancing learning outcomes. In the current project, pre-service teachers acquired scientific knowledge about learning strategies and their promotion in a computer-based learning environment. We explored the effect of different arrangements of signaling in classroom video-examples on conceptual knowledge and the reasoning-component of professional vision. Therefore, we conducted a set of two studies with 100 student teachers including two signal arrangements in order to investigate how signaling can help learning to reason about classroom videos. In addition, we varied if participants received information on the use of signals in advance (informed) or not (uninformed). We measured conceptual knowledge by asking participants what they knew about self-regulation strategies. Additionally, we assessed reasoning by asking participants to notice sequences in a video where teachers induced learning strategies, and to reason in what respect the observed behavior was useful to induce the strategy. Uninformed signaling did not affect the acquisition of conceptual knowledge and reasoning. Informed signaling led to significantly better conceptual knowledge than uninformed signaling. It is argued that the signal-induced extraneous load exceeded the load reduction due to the signal’s selection advantage in the uninformed conditions. In a third, exploratory study, nine participants were interviewed on the perception of different signals and indicated that spotlight and zoom-in signals foster processing of classroom videos.